Implementation Of Architecture Based Object Oriented Software System Reliability Prediction Model : Research Paper - Kashyap, Shailja; Srivastava, Durgesh (IJRDO -Journal of Computer Science Engineering, 2016)
Reliability of software system is the measure of extent to which a system can work efficiently and as expected, subjected to certain constraints and time period .Prediction or measurement of reliability of software system have been in lime light in world of software engineering researches .Multiple models and measurement tools have been designed to estimated the reliability based on different criteria for example, some models are based on failure rate, some on complexity matrix and others on system component failure probabilities .In this paper we introduce a system or software tool to predict object oriented software reliability at design and analysis phase .System is an implementation of already existing architecture based model , which makes use of annotated UML diagrams .The system output helps the user to easily calculate various failure probabilities and at the end over all system reliability ,at design phase itself, so the appropriate steps could be taken at an early stage .UML diagrams are created using UMLET software and the system have been developed in CPP .